ФЕНОМЕН ЦІННІСНІ ОРІЄНТАЦІЇ ДІТЕЙ СТАРШОГО ДОШКІЛЬНОГО ВІКУ В КОНТЕКСТІ СУЧАСНИХ ОСВІТНІХ СТАНДАРТІВ - Puyo , Olga (Науковий вісник Ужгородського університету. Серія: «Педагогіка. Соціальна робота», 2025)
Сучасне суспільство значну увагу приділяє інтелектуальному розвитку дітей. Емоційно-ціннісний розвиток дітей дошкільного віку довгі роки залишався поза увагою освітнього департаменту, батьків. Новий державний стандарт дошкільної освіти започаткував позитивні зрушення в цьому напрямку, однак проблема формування структури феномена ціннісних орієнтацій дітей старшого дошкільного віку є мало дослідженою, що посилює актуальність проблеми. Метою статті є розкрити структуру феномена ціннісні орієнтації дітей старшого дошкільного віку, його особливості у світлі освітніх реформаційних процесів. Дослідна робота проведена за допомогою методів аналізу, синтезу, індукції, дедукції, порівняння, систематизації, наукового узагальнення, діалектичного методу пізнання. Результатом дослідження є запропонований триступеневий інтеграл феномена ціннісні орієнтації дітей дошкільного віку із виокремленими складовими, компонентами, показниками та методами. Modern society pays considerable attention to the intellectual development of children. Emotional and value development of preschool children for many years remained out of the attention of the educational department, parents. The new state standard of preschool education has initiated positive changes in this direction, but the problem of the uniqueness of the formation of value orientations of older preschool children is little studied, which increases the urgency of the problem. The aim of the article is to reveal the structure of the phenomenon of value orientations of older preschool children, its features in the light of educational reformation processes. The article highlights the components of the phenomenon of value orientations of older preschool children: emotional, semantic, and activity. It highlights the components that correspond to these components: emotional-volitional, cognitive, and activity. The criteria of each component are defined: emotional-volitional – sensory-oriented criterion, cognitive – knowledge-oriented, activity - operational. These criteria are met by indicators of the formation of value orientations of older preschool children. Indicators of understanding the emotions, the expression of compassion, the ability to control emotions correspond to the sensory-oriented criterion; knowledge-oriented criterion includes the presence of knowledge about the values of interaction, empathy and friendship, the content and rules of mobile games, the rules of conduct in the game; operational criterion is responsible for the ability to express emotions and respond to the emotions of others, follow the rules of the game, take responsibility, initiate and establish interaction between all participants in the game. The research work was carried out using the methods of analysis, synthesis, induction, deduction, comparison, systematization, scientific generalization, dialectical method of cognition. As a result of the study we provide three-stage integral of the phenomenon of value orientations of preschool children with selected components, components, indicators and methods.